Versatile identity-based signatures for authentication in multi-user settings. (1st January 2014) - Sun, Xi; Jiang, ZhengTao; Zhou, MeiRong; Wang, Yumin
This paper proposes a new identity-based signature scheme. The new scheme is proven to be existentially unforgeable against Chosen-Principle and Chosen-Message (CP-CM) attackers who are the strongest attackers so far defined for identity-based signatures. The security of our scheme relies on the standard Computational Diffie-Hellman (CDH) assumption. The proof is given in the random oracle model where a hash function is modeled as random oracle. Analysis shows that our scheme is also more efficient than the state of the art in terms of computation and communication. We finally improve the basic scheme by eliminating the singlepoint problem, allow using as a proxy signature scheme and enable fast verification in multi-user settings. The basic scheme and its extensions show that our proposal is versatile to realise efficient and secure authentication in various scenarios.